Reactivation of fungal spores in water following UV disinfection: Effect of temperature, dark delay, and real water matrices. (December 2019) - Wen, Gang; Wan, Qiqi; Deng, Xiaoli; Cao, Ruihua; Xu, Xiangqian; Chen, Zhuhao; Wang, Jingyi; Huang, Tinglin
Abstract: The occurrence of fungi in water supply systems causes many environmental problems (e.g., odor, taste, turbidity, formation of mycotoxins); it has been an area of increasing concern in recent years. Ultraviolet irradiation can inactivate fungi efficiently. However, its reactivation poses further challenges in water purification. The reactivation characteristics of waterborne fungi under different environmental conditions have rarely been reported. In this study, the effects of temperatures and dark delay on the reactivation of three genera of fungal spores ( Trichoderma harzianum, Aspergillus niger, Penicillium polonicum ) were evaluated. The reactivation levels among these fungal spores were compared in phosphate buffer solution (PBS) and in real groundwater. It was found that lower temperature can inhibit the photoreactivation of fungi, whereas higher temperatures would promote the process. A long-term dark delay can inhibit the photoreactivation of fungi effectively. The dark repair of fungal spores almost do not occur neither in PBS nor in real groundwater. Finally, the photoreactivation percentage in real groundwater was higher than that in PBS. This study will provide a basis for controlling the reactivation of fungi in water. Graphical abstract: Image 1 Highlights: Waterborne fungi own the ability of repairing DNA damage caused by UV irradiation. Temperature is positively correlated with the photoreactivation of fungi. A long term dark delay can attenuate the photoreactivation of fungi effectively. Photoreactivation percentage of fungi in real groundwater was higher than that in PBS.